2019
DOI: 10.1021/acs.iecr.9b03134
|View full text |Cite
|
Sign up to set email alerts
|

A Debottlenecking Study of an Industrial Pharmaceutical Batch Plant

Abstract: Operational complexity in batch-operated plants is large and companies struggle 3 to produce at high equipment utilisation. Due to high xed costs, capacity utilisation 4 is an important operational directive. Many current plants are not in a state that 5 allows the application of rigorous process systems engineering tools due to modelling 6 challenges. This work proposes identifying the right engineering projects based on 7 statistic evidence. In the case of incomplete process monitoring strategies in semi-8 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The inherent complexity of multiproduct batch plants indicates that it is already a substantial challenge to operate plants at high capacity utilization. 6 Due to high capital investiture, this is often the pressing operational objective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inherent complexity of multiproduct batch plants indicates that it is already a substantial challenge to operate plants at high capacity utilization. 6 Due to high capital investiture, this is often the pressing operational objective.…”
Section: Discussionmentioning
confidence: 99%
“…3 Moreover, the bioeconomy is already an established industry sector with countless plants in operation, which in 2014 in the European Union generated 2.2 trillion Euro in turnover. 4 While it seems that no exhaustive comparative study exists in open literature, case studies 5,6 as well as small production scales, batch operation, and lacking online sensor technology indicate that bioprocesses are operated at lower levels of automation than a wide range of chemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…Our determined potential savings of 50% campaign duration, and of up to 14% labor costs, highlight the significance of this approach. Other less complex optimization attempts, as published by Bähner et al, who evaluated the machine utilization, benefit from the fact, that the time-consuming modeling is not required [30]. However, only the processor utilization is mapped and the operator utilization is disregarded.…”
Section: Discussionmentioning
confidence: 99%
“…The next step of model validation is already described as being a crucial point for model-based debottlenecking approaches. Irregular or unsteady production steps are known to complicate or even preclude a successful model validation [30]. Unfortunately, unfavorable circumstances also led to a failed predictive model validation.…”
Section: Case Study Outcomesmentioning
confidence: 99%
“…This difference in the nature of the operation of a batch plant has been recognized by process systems engineers, who have, in turn, offered a wealth of literature on the design and optimal operation of such flexible batch plants. This includes work on the optimal operation of a single batch unit as well as the optimal design and scheduling of multipurpose units. These studies have shown that the effect of flexibility on the overall process economics may be considerable. For example, Goršek et al used a case study from the specialty chemicals industry to demonstrate that, while the continuous operating mode is superior to the batch operating mode for all plant capacities if single-purpose equipment is considered, the batch operating mode becomes more profitable at low product demands when multipurpose equipment is considered.…”
Section: Introductionmentioning
confidence: 99%